2022
DOI: 10.3389/finsc.2022.829869
|View full text |Cite
|
Sign up to set email alerts
|

A Detoxification Enzyme for Apis mellifera Newly Characterized by Recombinant Expression: 10-Formyl Tetrahydrofolate Dehydrogenase

Abstract: Honeybees are important managed pollinators that perform important ecological and economic functions. In recent decades, the obligate ectoparasite Varroa destructor severely affected survival of honeybees as it either feeds on hemolymph and fat bodies or acts as a vector for viruses. A common treatment against the varroa mite is formic acid, which has been used for many years by beekeepers. This treatment is known to be effective, but the therapeutic index is very narrow. Many beekeepers report negative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The dehydrogenase activity was measured by monitoring the increase in absorbance at 340 nm. The recombinantly expressed wildtype protein showed an enzyme activity with a Vmax of 0.1846 nM•min −1 to 0.4253 nM•min −1 at different pH and Km values of 2.455 µ M up to 9.596 µ M (according to previously published data [22]). The mutations lost their activity almost entirely, with values ranging between 0.007 nM•min −1 and 0.12 nM•min −1 for their Vmax values and between The superimposed structure of the AlphaFold2 model and the bound-form homology model differed in the loop position (Figure 3B).…”
Section: Enzyme Kineticssupporting
confidence: 74%
See 2 more Smart Citations
“…The dehydrogenase activity was measured by monitoring the increase in absorbance at 340 nm. The recombinantly expressed wildtype protein showed an enzyme activity with a Vmax of 0.1846 nM•min −1 to 0.4253 nM•min −1 at different pH and Km values of 2.455 µ M up to 9.596 µ M (according to previously published data [22]). The mutations lost their activity almost entirely, with values ranging between 0.007 nM•min −1 and 0.12 nM•min −1 for their Vmax values and between The superimposed structure of the AlphaFold2 model and the bound-form homology model differed in the loop position (Figure 3B).…”
Section: Enzyme Kineticssupporting
confidence: 74%
“…On one hand, Tsybovsky and Krupenko [46] have already shown that the residues C707 and E677 are important for the degradation of 10-formyl tetrahydrofolate in Rattus norvegicus. However, on the other hand, the conservation of this enzyme between the two species A. mellifera and R. norvegicus is so low [22] that confirmation of the active site is necessary to make further functional statements. The expected molecular mode of action is as follows: first, glutamate E673 and cysteine C707 are hydrogen-bonded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation